2020
DOI: 10.1093/jas/skaa117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper and zinc sources and inclusion levels of copper on weanling pig performance and intestinal microbiota

Abstract: A 42-d experiment was conducted to evaluate the effect of Cu and Zn source and Cu level on pig performance, mineral status, bacterial modulation, and the presence of antimicrobial-resistant genes in isolates of Enterococcus spp. At weaning, 528 pigs (5.9 ± 0.50 kg) were allotted to 48 pens of a randomized complete block design in a 2 × 2 factorial arrangement with two Cu and Zn sources (SF: sulfate and HCl: hydroxychloride) and two Cu levels (15 and 160 mg/kg). As a challenge, the pigs were reared in dirty pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
3
32
0
1
Order By: Relevance
“…For instance, the supplementation of weanling pig diets with Cu hydroxychloride decreased the oxidative stress in the duodenum (Fry et al., 2012; Huang et al., 2015) and increased the serum activity of SOD and ceruloplasmin (Zheng et al., 2018) compared to Cu sulphate. Likewise, the supplementation of Cu and Zn hydroxychloride tended to increase serum GPx activity in weaned pigs (Villagómez‐Estrada, Pérez, Darwich, et al, 2020). Although the absorption and retention rates of trace mineral sources were not measured, a greater apparent total tract digestibility was observed for Zn and Cu hydroxychloride, suggesting a better absorption, and therefore less faecal excretion, compared to sulphates.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the supplementation of weanling pig diets with Cu hydroxychloride decreased the oxidative stress in the duodenum (Fry et al., 2012; Huang et al., 2015) and increased the serum activity of SOD and ceruloplasmin (Zheng et al., 2018) compared to Cu sulphate. Likewise, the supplementation of Cu and Zn hydroxychloride tended to increase serum GPx activity in weaned pigs (Villagómez‐Estrada, Pérez, Darwich, et al, 2020). Although the absorption and retention rates of trace mineral sources were not measured, a greater apparent total tract digestibility was observed for Zn and Cu hydroxychloride, suggesting a better absorption, and therefore less faecal excretion, compared to sulphates.…”
Section: Discussionmentioning
confidence: 99%
“…Since in the present study pigs were offered nutritional and high doses of Cu at the same time, no distinctions in growth performance could be established. However, in a previous study performed in our laboratory, the supplementation of weanling pig diets with 160 mg Cu/kg increased ADFI (360 to 379 g), gain to feed ratio and BW(16.6 to 17.7 kg) compared to diets with 15 mg/Cu kg after 42 days of administration ( p < 0.05) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies showed that the selenium supplementation increases the microbial diversity, and that the many species are selenium-dependent competing with the host on the selenium availability ( 175 ) and contributing to the metabolism of the seleno-proteins ( 176 ). Zinc and copper supplementation in pigs at the weaning age showed also decrease levels of Streptococcus, Enterobacter and Escherichia , and increased levels of Lachnospira and Roseburia ( 177 ). No studies are available on the effect of minerals on the gut microbiota of children affected by T1D, however there are clear evidences of micronutrients deficiencies in T1D adult population ( 178 ) and of the beneficial effect of antioxidant vitamins C and E on endothelial function in T1D cohort ( 179 ).…”
Section: Early Nutrition As Modulator Of Microbiota In Relation To T1mentioning
confidence: 99%